Millimetre-Wave Metamaterial-Based Sensor for Characterisation of Cooking Oils - Suhail Asghar Qureshi; Zuhairiah Zainal Abidin; Adel Yahya Isa Ashyap; Huda A. Majid; Muhammad Ramlee Kamarudin; Ma Yue; Mohd Syis Zulkipli; Jamel Nebhen (International Journal of Antennas and Propagation)
The characterisation of the cooking oils presents a significant challenge due to minor changes in their dielectric behaviour. In this paper, a new metamaterial-based sensor incorporating a split-ring resonator (SRR) with a microstrip transmission line is presented to characterise cooking oils. The design demonstrates metamaterial characteristics of negative permittivity and permeability simultaneously at the resonance frequency. Furthermore, its operation in the range of millimetre-wave frequencies can further enhance its sensitivity, especially for liquid materials. The sensor’s novelty is the operation at millimetre-wave frequencies that offers a high shift in the transmission coefficient while operating at 30 GHz. The sensor’s performance analysis is undertaken by using six MUTs with dielectric constants ranging from 0.126 to 4.47. The presented structure designed on 12 × 8 mm2 Rogers substrate offers a sensitivity of 1.12 GHz per unit change in dielectric constant. The phase's shift demonstrates a lower percentage error than the amplitude and linearly moves towards higher frequencies with the increase in dielectric constant and tangent loss of MUT. The designed sensor can be prominently useful for detecting liquids' chemical characteristics in chemistry and medicine fields.